2009
DOI: 10.1111/j.1477-9552.2009.00209.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Impacting Food Safety Risk Perceptions

Abstract: We developed and applied a model of consumer risk perceptions of beef food safety to better understand the underlying drivers of consumer demand for food safety. We show how consumer demographics, country-of-residence, as well as reliance on, and trust in, alternative food safety information sources affect risk perceptions of consumers in Canada, Japan and the United States. Consumers in all three countries have risk perceptions shaped by their level of reliance on observable and credence attribute information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 44 publications
1
37
0
5
Order By: Relevance
“…Also, branding tied to a particular retailer or store can help to promote and ensure confi dence and loyalty. Tonsor, Schroeder, and Pennings (2009) concluded that store reputation infl uences consumer perceptions about products' quality and safety and that store branding is an additional way to leverage value from a store's reputation. We expect store brands to play a substantial and growing role in branded beef products in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Also, branding tied to a particular retailer or store can help to promote and ensure confi dence and loyalty. Tonsor, Schroeder, and Pennings (2009) concluded that store reputation infl uences consumer perceptions about products' quality and safety and that store branding is an additional way to leverage value from a store's reputation. We expect store brands to play a substantial and growing role in branded beef products in the future.…”
Section: Discussionmentioning
confidence: 99%
“…It implies a shared responsibility of the stakeholders within the farm to fork continuum (producers, processors, trading companies, retailers and consumers) and those closely involved in supporting food safety in the supply chain (competent authorities, industry associations, food scientists). Several studies measured the perceptions of consumers on various aspects of food safety (Sparks & Shepherd, 1994;Grunert, 2005;Tonsor, Schroeder, & Pennings, 2009;Nielsen et al, 2009;Soon-Mi et al, 2011). A limited number of studies on opinions of key stakeholders (experts) on food safety policy are available (van Kleef et al, 2006;Sargeant et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…La importancia de conocer la percepción de riesgo para la salud por parte de los consumidores, sobre la inocuidad de la carne, radica en que permite una mejor comprensión de los factores que determinan la demanda y para mejorar el diseño de estrategias de la industria para contrarrestar movimientos negativos de la demanda (23) . Los consumidores percibieron que la carne está contaminada (80 %) en algún grado con sustancias o microorganismos que pueden dañar la salud.…”
Section: Resultsunclassified